2017
DOI: 10.3390/rel8090191
|View full text |Cite
|
Sign up to set email alerts
|

Prayer, Meditation, and Anxiety: Durkheim Revisited

Abstract: Durkheim argued that religion's emphasis on the supernatural combined with its unique ability to foster strong collective bonds lent it power to confer distinctive social benefits. Subsequent research has confirmed these propositions with respect to religion and mental health. At the same time, meditation has been linked to mental health benefits in intervention-based studies. Our investigation offers a unique test of two comparable inhibitors of anxiety-related symptoms in the general population, namely, pray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…For those who did not participate in religious activities, whether they had a religious identity or not, social relationships were found to help increase their happiness. These results may shed new light on previous findings that religion could work as a substitution for social relationships and, as such, enhance a sense of happiness [67]. The current research further discovered that it is not religious identity but, rather, religious practice that exerts a substitution effect in terms of social relationships.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For those who did not participate in religious activities, whether they had a religious identity or not, social relationships were found to help increase their happiness. These results may shed new light on previous findings that religion could work as a substitution for social relationships and, as such, enhance a sense of happiness [67]. The current research further discovered that it is not religious identity but, rather, religious practice that exerts a substitution effect in terms of social relationships.…”
Section: Discussionsupporting
confidence: 75%
“…This builds on previous research, such as that of Durkheim [68], which emphasized religion’s social function as benefiting mental health. Likewise, Bartkowski et al [67], grounded in Durkheim’s approach, found that only communal prayer can yield anxiety-reducing benefits. The present research takes a step further in uncovering that religious practice shares certain intrinsic similarities with social relationships, on account of the people involved seeking psychological consolation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, all this has broad, important implications in terms of general well-being and, more specifically, mental health. Generally, most studies have found a positive impact of religiosity/spirituality on perceived health-related quality of life and health (see (Bartkowski et al 2017) for review studies). Correlational investigations have reported meaningful associations between spiritual tendencies and internal locus of control, with the latter mediating the relationship between religiosity and health and well-being (Jackson and Coursey 1988;Ryan and Francis 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A long and ever-growing research tradition has identified mental health benefits of public or organizational forms of religious involvement. Indeed, people who regularly attend religious services display lower rates of depression (Idler, McLaughlin, and Kasl 2009), lower rates of anxiety (Bartkowski, Acevedo, and Van Loggerenberg 2017), and higher life satisfaction (Krause 2003) compared to those who do not attend services or who attend on a more sporadic basis. Moreover, religious attendance has been identified as the strongest predictor of wellbeing compared to more private dimensions of religiosity, such as prayer or belief salience (Fenelon and Danielsen 2016;Vanderweele 2017).…”
mentioning
confidence: 99%